Antonio Gramsci between (International / National) Social Struggles and Intellectual Contexts - Gómez, Sebastián (International Gramsci Journal, 2023)
This is the Abstract of the English-language review by Sebastián Gómez of the book by Gianni Fresu Antonio Gramsci. A Political Biography published by Palgrave Macmillan (Springer Group), 2022.